THE RELATIONSHIP BETWEEN INTEREST INDEPENDENT AND PARENT'S ATTENTION WITH MATHEMATICS LEARNING OUTCOMES - Estu Pungkastuti; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The mathematics students are learning outcomes are associated with many factors. Interest independent and parents attention some of the factors related to learning outcomes. This study aims to determine the presence or absence of a positive and significant relationship between interest independent and parents attention with learning achievement mathematics comes students class VIII Islamic Junior High Scool (MTs) Muhammadiyah Karangkajen Yogyakarta semester in the academic year of 2016/2017. This study's population is all students of class VIII MTs Muhammadiyah Karangkajen Yogyakarta semester in the academic year of 2016/2017, consisting of 5 classes with 151 students. The experimental class and the sample class were taken by random sampling technique to the class. They obtained the trial class VIII A and VIII B as the sample class. The technique of collecting data is done by test, questionnaire method, and interview. The instrument using the test, questionnaire method, and interview. Test the instrument using the validity test, a test of different power and reliability test. Test prerequisite analysis that is normality test, independent test, and linearity test. Analysis of data using product-moment correlation analysis and multiple linear regression analysis.             The results showed a positive and significant relationship between independent interest and parents' attention to mathematics learning. Students class VIII in even Semester of MTs Muhammadiyah Karangkajen Yogyakarta semester in 2016/2017. It is showed by Fcount = 5.8345  Ftable= 3.3541 with R = 0.5493 and R2 = 0.3018 with , with RC = , RC = , EC = , EC = .